Impact of the Breakpoint Region on the Leukemogenic Potential and the TKI Responsiveness of Atypical BCR-ABL1 Transcripts - Massimino, Michele; Tirrò, Elena; Stella, Stefania; Manzella, Livia; Pennisi, Maria Stella; Romano, Chiara; Vitale, Silvia Rita; Puma, Adriana; Tomarchio, Cristina; Di Gregorio, Sandra; Antolino, Agostino; Di Raimondo, Francesco; et al. (Frontiers in Pharmacology, 2021)
Chronic Myeloid Leukemia (CML) is a hematological disorder characterized by the clonal expansion of a hematopoietic stem cell carrying the Philadelphia chromosome that juxtaposes the BCR and ABL1 genes. The ensuing BCR-ABL1 chimeric oncogene is characterized by a breakpoint region that generally involves exons 1, 13 or 14 in BCR and exon 2 in ABL1. Additional breakpoint regions, generating uncommon BCR-ABL1 fusion transcripts, have been detected in various CML patients. However, to date, the impact of these infrequent transcripts on BCR-ABL1-dependent leukemogenesis and sensitivity to tyrosine kinase inhibitors (TKIs) remain unclear. We analyzed the transforming potential and TKIs responsiveness of three atypical BCR-ABL1 fusions identified in CML patients, and of two additional BCR-ABL1 constructs with lab-engineered breakpoints. We observed that modifications in the DC2 domain of BCR and SH3 region of ABL1 affect BCR-ABL1 catalytic efficiency and leukemogenic ability. Moreover, employing immortalized cell lines and primary CD34-positive progenitors, we demonstrate that these modifications lead to reduced BCR-ABL1 sensitivity to imatinib, dasatinib and ponatinib but not nilotinib. We conclude that BCR-ABL1 oncoproteins displaying uncommon breakpoints involving the DC2 and SH3 domains are successfully inhibited by nilotinib treatment.